The influence of Micro-Finance Institutions (MFIs) on Micro and Small Enterprises (MSEs) in Kenya - Ngatia, Ndiritu (Rhodes University, Faculty of Commerce, Investec Business School, 2007)
In Kenya, like in many developing countries, Micro and Small Enterprises (MSEs) have become the main focus for achieving the much-needed social and economic development and alleviating poverty. However, their development has been hampered by lack of access to appropriate financial and related services. Micro financing has been seen as a viable alternative to providing financial services to entrepreneurs in the MSE sector. The focus of this study was to explore the role of MFIs in the development of MSEs and to see if there are ways in which this role can be enhanced to better support the growth of MSEs. Such enhancement would contribute greatly towards government efforts to foster social-economic development. The results of the research indicate that generally, MFIs appear to have positively influenced the growth of MSE in Kenya and have potential to further influence MSE growth. There were however a number areas that if paid attention to could enhance this influence. These include the need for MFIs to offer supportive services as opposed to merely credit facilities to MSEs and the need for government intervention by putting in place a suitable Act to regulate the operations of MFIs.
Keywords: Microfinance -- Kenya; Financial institutions -- Kenya; Small business -- Kenya